Stem Cell Drugs - A New Generation of Biopharmaceuticals (Stem Cells in Clinical Applications,, 2018)
This invaluable resource discusses the current revolution in stem cell-based drugs and their potential use in clinical applications. Each chapter is contributed by a pre-eminent scientist in the field. An introductory section presents current stem cell drugs and stem cell-based products and a discussion of production, quality control, mechanisms, and efficacy. Following sections include discussions on stem cell-derived microvesicles based products, and derived exosomes based products. Stem Cell Drugs - A New Generation of Biopharmaceuticals and the other books in the Stem Cells in Clinical Applications series are invaluable to scientists, researchers, advanced students and clinicians working in stem cells, regenerative medicine or tissue engineering. This groundbreaking volume is also essential reading for those researching or studying drug development or pharmaceutical science. .